Smartphone Use as Necessity and Risk: Examining Its Impact on Anxiety, Depression, and Social Isolation Among Students in AJK - Ishaque, Samyyia; Tariq, Ammama; Ashfaq, Haseena; Zahid, Summon (ACADEMIA International Journal for Social Sciences, 2025)
The present study, titled “Smartphone Use as Necessity and Risk: Examining Its Impact on Anxiety, Depression, and Social Isolation among Students in AJK,” investigated the dual role of smartphones in students’ academic and psychological lives. While smartphones are essential tools for communication, learning, and information access, excessive and problematic use may pose risks to mental well-being. This study employed a quantitative, cross-sectional correlational research design. Data were collected from 300 university students in Azad Jammu and Kashmir using the Smartphone Addiction Scale–Short Version (SAS-SV), the Pittsburgh Sleep Quality Index (PSQI), and the Depression Anxiety Stress Scale (DASS-21). Data were analyzed using SPSS through reliability analysis, descriptive statistics, Pearson correlation, regression analysis, and mediation analysis using PROCESS Macro (Model 4).The findings revealed moderate levels of problematic smartphone use and poor sleep quality among students, along with mild to moderate levels of anxiety and depression. Significant positive relationships were found between problematic smartphone use and anxiety, depression, and social isolation. Regression analysis indicated that problematic smartphone use significantly predicted psychological distress. Furthermore, sleep quality partially mediated the relationship between problematic smartphone use and mental health outcomes, suggesting that excessive smartphone use contributes to distress both directly and indirectly through sleep disruption.The study underscores the dual nature of smartphones as both academic necessities and potential psychological risk factors. The findings highlight the need for balanced smartphone use and digital well-being interventions to promote healthier academic and social environments among students in AJK.